RANCANG BANGUN RANGKA PEMBANGKIT LISTRIK PORTABLE DENGAN MENGGUNAKAN PEMBANGKIT LISTRIK TENAGA BAYU DAN PEMBANGKIT LISTRIK TENAGA SURYA - Yudi Siswanto; Amiruddin Amiruddin; Ika Nurjannah; Miftahul Khair (Otopro)
Electrical energy sources have developed rapidly today in order to minimize the use of fuel oil which is currently decreasing in number and the distribution of electricity from PLN to the community which is not evenly distributed. The use of renewable and environmentally friendly energy will provide a solution when compared to the use fuels fossil  such as coal which will soon run out, it is also known that Indonesia is a coastal country with abundant wind speed and sunlight potential. Therefore, this study aims to create a power generator by utilizing the potential of solar power plant (PLTS) and wind power plant (PLTB) energy sources by adding a portable system is designed using solidworks. In the process of making this tool, planning is carried out to make a design, design determines the tools and materials used, the work process, cutting hollow iron according to the specified size, welding, and installation of windmills. The size of this power plant is 1330mm long, 600mm wide and 700mm high. The results of the portable power plant test using a 15W capacity lamp obtained the highest results at 11.05VDC PLTS and the highest voltage at 2.45VDC PLTB. In addition, this study also carried out a safety factor simulation on the power plant frame from the simulation results obtained as follows in part one stress value (vonmises) 9.873e-08N/m2, displacement 3.930e-04 mm, strain 4.637e+04 N/m2, and safety factor 1.741, In the frame section two stress (vonmises) 5.554e-04N/m2, displacement 3.098e-00mm, strain 9.488e-08N/m2, and safety factor 3.6.